Assessing the Photoinduced Electron-Donating Behavior of Carbon Nanodots in Nanoconjugates - Ferrer-Ruiz, Andres; Scharl, Tobias; Rodriguez-Perez, Laura; Cadranel, Alejandro; Angeles Herranz, M.; Martin, Nazario; Guldi, Dirk Michael (Journal of the American Chemical Society, 2020)
Carbon nanodots (CNDs) undergo electron transfer in different scenarios. Previous studies have mainly focused on the electron-accepting features of CNDs in covalently linked donor-acceptor nanoconjugates. In view of this, we decided to carry out in this study the formation of covalently linked nanoconjugates that feature electron-donating pressure synthesized carbon nanodots (pCNDs) and electron-accepting 11,11,12,12-tetracyano-9,10-anthra-p-quinodimethane (TCAQ): pCND-TCAQ The stability of the one-electron reduced form of TCAQ renders it the acceptor of choice. Detailed structural and electrochemical investigations allowed the characterization of pCND-TCAQ Furthermore, investigations regarding intramolecular interactions, by means of steady-state and pump-probe transient absorption spectroscopies, allowed detection and characterization of three excited state species, in general, and the pCND(center dot+)-TCAQ(center dot-) charge-separated state, in particular.
CRIS-Team WoS Importer:2021-02-05